NOTAS PARA UNA LECTURA POLITICA DE LA OBRA DEL BEATO DE LIEBANA - Corella Lacasa, Miguel (Res Publica. Revista de Historia de las Ideas Políticas, 2023)
A political interpretation is made of the whole of Beato de Liébana’s works, in which they are seen in the historical context of the adoptionist controversy, as an attack on Archbishop Elipando de Toledo, and the theological foundation ot the Asturian monarchy. The key to the apocalyptic myth, which is not millenarianist but rather connected to the political practices of legitimisation in the face of the archbishopric of Toledo, is fundamental in order to understand the political repercussions of Beato, whose concept of history acted as the basis for the justification of the medieval monarchy. In this work the ways in which these political aspirations were represented through the use of metaphors is analysed.
Keywords: Apocalypse; Myth; Metaphor; Adoptionist heresy; Kingdom of Asturias